Devouring darkness : an Heirs of Chicagoland novel - Neill, Chloe (Neill, Chloe. Heirs of Chicagoland novels, 2022)
"In the newest installment of the USA Today bestselling Heirs of Chicagoland series, vampire Elisa Sullivan unearths an ancient grudge, with potentially devastating consequences. As the only vampire ever born, and the daughter of two very powerful Chicago vampires, Elisa Sullivan knew her life was going to be...unusual. But she wanted to make her own way in the world, preferably away from her famous family. Then supernatural politics-and perhaps a bit of destiny-intervened, and Elisa had to steady her nerves and sharpen her steel to fight for the city of Chicago. Luckily, Connor Keene, son of the North American Central Pack's Apex wolf, is right by her side. When Elisa and her Ombudsman colleagues agree to escort a troubled sorceress to Chicago, they inadvertently set in motion a scheme of long-awaited magical vengeance. The city may pay an arcane price it can't afford unless Elisa and her allies rise to the challenge"--